HUBUNGAN MEROKOK DENGAN KEJADIAN HIPERTENSI PADA LAKI – LAKI USIA DEWASA AWAL (18 - 25 TAHUN) DI DESA MEDALI KECAMATAN PURI KABUPATENMOJOKERTO - Triwibowo, Heri; Frilasari, Heni (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Hypertension or high blood pressure is often referred to as the silent killerbecause the patient does not know that he was suffering from hypertension. Hypertension, also known as heterogenouse group disease because it can affect anyone of age groups, social, and economic. Hypertension is systolic and diastolic pressures increasing with consistency above 140/90 mmHg. Hypertension often causes changes in blood vessels that can lead to increasing blood pressure. One of the causes of hypertension are smoking behavior is a bad habit that a person in everyday life that could harm and endanger yourself and the people around. The Society. The purpose of this study was to determine the incidence of hypertension Smoking Relationship Age Adult Early (18 - 25 years ) in Medali village,PuriSubdistrict, Mojokerto District. The used method is that Case control study (retrospective), the population is respondents who smoked as many as 106 people. Sampling techniques in this study using nonprobability with purposive sampling type. The sample in this study according to the inclusion criteria of 52 respondents. Independent variables were smoking and the Dependent Variablesis the incidence of hypertension. Data is collected by spreading questionnaire and blood pressure measurements. Dissemination of research results by using the Spearman rho test with SPSS V.16.0. The results showed p (0.000) < α (0.05). It means that H0is rejected, there is a smoking Relations with hypertension early adulthood (18 - 25 years) in Medali village,PuriSubdistrict, Mojokerto District. Which is expected to improve understanding of the importance of health.Key words: Early adulthood men, Hypertension,Smoking